Diagnostic Performances of Clinical and Hematological Parameters in Cats Naturally Infected with Feline PanleukopeniaVirus: Clinical Parameters in Cats with Feline Panleukopenia Virus - Gülersoy, E; Balıkçı, C; Erol, BB; Şahan, A; Günal, İ (Journal of the Hellenic Veterinary Medical Society, 2023)
Feline panleukopenia (FP) virus, which is closely related to canine parvovirus, is a fatal viral disease that affects mitotically active tissues such as intestinal cells, lymphoid tissue and bone marrow in cats of all ages and causes a wide variety of clinical findings. Despite its high incidence, there is still a need for studies on the effectiveness of demographic, routine clinical and hemogram data on the diagnosis of FP, which has not been investigated as much as canine parvoviral infection. The Panleukopenia Group of the study consisted of 50 naturally infected cats with panleukopenia, and the Control Group consisted of 10 healthy cats of similar age and body weight. Information on sex, age, body weight, breed and origin of all cats was recorded. Venous blood samples were obtained from the cats eligible for inclusion in the study, and the diagnostic efficacy of clinical examination findings and demographic data along with hemogram parameters were investigated. Most of the Panleukopenia Group cats were indoor and were bought from a breeder. The most prominent clinical finding of the diseased cats was loss of appetite. This was followed by dehydration, stagnation, depression, vomiting, diarrhea and ocular discharge. In clinical examination, respiratory rate, pulse and body temperature values were higher in the Panleukopenia Group (p< 0.017). As a result of hemogram analysis, it was determined that WBC, lymphocyte, monocytes, granulocytes, RBC, Hct, RDW, Hb and THR levels were lower in the Panleukopenia Group (p< 0.040). As a result of the ROC analysis, it was determined that from clinical examination parameters, respiratory rate had excellent, pulse and body temperature had good; from hemogram parameters, WBC and granulocyte had outstanding, lymphocyte and RDW had excellent, monocytes, Hct and THR had good, RBC and Hb had acceptable diagnostic performances. As a result, it was concluded that demographic data and clinical findings along with abnormal leukograms such as leukopenia, lymphopenia and granulocytopenia and abnormal hemogram patterns such as anemia and thrombocytopenia may be helpful in the diagnosis of FP in triage and in cases where antibodies bind to viral epitopes resulting in false negatives.